The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1259/bjr.20160508
|View full text |Cite
|
Sign up to set email alerts
|

Predicting risk factors for radiation pneumonitis after stereotactic body radiation therapy for primary or metastatic lung tumours

Abstract: Subclinical ILD was the only significant factor for Grade 2-5 RP. In addition, the cases with honeycombing had a high potential for fatality related to severe RP. Patients with subclinical ILD should be carefully monitored for the occurrence of severe RP after SBRT. Advances in knowledge: Hypofractionated SBRT for primary or metastatic lung tumours provides a high local control rate and safe treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 45 publications
(55 reference statements)
0
16
1
Order By: Relevance
“…It is true that symptomatic RILI is important, and many reports have emphasized the predicting factors of symptomatic RILI. However, the comorbidities of the patient, baseline respiratory function, subclinical interstitial lung disease, performance status or subjectivity of physicians can affect symptomatic complaints [ 10 15 ]. Thus, the radiological appearance of RILI is not always accompanied by clinical symptoms [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is true that symptomatic RILI is important, and many reports have emphasized the predicting factors of symptomatic RILI. However, the comorbidities of the patient, baseline respiratory function, subclinical interstitial lung disease, performance status or subjectivity of physicians can affect symptomatic complaints [ 10 15 ]. Thus, the radiological appearance of RILI is not always accompanied by clinical symptoms [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Figure 4 shows strong correlation between V 5 , V 13 ,V 20 and MLD for the UCSD cohort with large and significant Spearman’s rank-order correlation coefficients, (Rs ≥ 0.931, p < 0.001). Effect of possible confounders, specifically pulmonary emphysema, tumor location (upper/middle vs lower) and ILD was studied in the original report for the cohort A [ 21 ]. ILD was the only factor significantly associated with RP.…”
Section: Resultsmentioning
confidence: 99%
“…Two patient cohorts from previously reported studies were used, referenced below as cohorts A [ 21 ] and B [ 22 ]. These studies were selected because they provided detailed patient-specific data in a tabulated form.…”
Section: Methodsmentioning
confidence: 99%
“…Zhao et al (78) analyzed pooled data and showed that older age, larger tumor size, the mean lung dose, and the volume of lung receiving a dose of more than 20 Gy are all associated with an increased risk of developing radiation pneumonitis. In the findings from a retrospective analysis, Okubo et al (79) showed that the presence of preexisting CT changes of interstitial pneumonitis was an independent predictor for development of post-SBRT radiation pneumonitis. The depiction of honeycombing on CT images had a high potential for fatality related to severe radiation pneumonitis (79).…”
Section: Radiation Pneumonitismentioning
confidence: 99%
“…In the findings from a retrospective analysis, Okubo et al (79) showed that the presence of preexisting CT changes of interstitial pneumonitis was an independent predictor for development of post-SBRT radiation pneumonitis. The depiction of honeycombing on CT images had a high potential for fatality related to severe radiation pneumonitis (79).…”
Section: Radiation Pneumonitismentioning
confidence: 99%